BERBAGAI VARIAN TARIPADA ACARA PESTA PERKAWINAN - Merianti Sabriana; Ernida Kadir; Asmaryetti Asmaryetti (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This paper discusses the low appreciation of dancers for the designation of dance at weddings. Under these conditions, the bride and groom are similar to the one-day King and Queen, who deserve to be respected. Ignoring the direction of facing in dance performance as an indication of the form of joyful respect for the bride and groom becomes a problem. This neglect can be seen in the dancer's position when the show always faces the audience and turn sits back to the bride and groom as the main character in the wedding ceremony. Such behavioris called discord in Minangkabau terminology. That is, behavior that does not conform to custom. The discordant performance by the dancers and the absence of evaluation from various parties became the fulcrum of the analysis of this study was carried out. Thus, this question explains phenomena and describes reality through qualitative research, using descriptive methods, and then analyzes through various related theories, namely normative ethics theory, structural theory, and performing arts theory.